Malay essay writing module based on thematic approach for non-native speaker: a need analysis in primary schools - Austrus, Edmund; Mahamod, Zamri; Adnan, Nor Hafizah (International Journal of Evaluation and Research in Education (IJERE), 2025)
The challenges faced by non-native speaking pupils in primary schools, characterized by diverse backgrounds, highlight the difficulty in teaching and learning essay writing. This study was conducted to identify the needs for the development of a Malay language essay writing module based on a thematic approach through the needs analysis phase. This qualitative study was conducted among Malay language teachers in Sarawak. Eight teachers were purposively sampled, and thematic analysis was employed for data analysis. The findings found that there are six themes that have been identified, namely: i) relevant form of teaching and learning in essay writing; ii) relevant teaching and learning resources; iii) relevant teaching and learning activities; iv) relevant teaching and learning strategies; and v) the needs of the thematic approach in essay writing; vi) the needs for the development of thematic-based essay writing module. The findings underscore the imperative development of a Malay essay writing module based on a thematic approach to enhance the essay writing proficiency of non-native-speaking pupils. Furthermore, the study's insights offer valuable guidance for researchers in designing and developing modules during the subsequent phases, contributing to the refinement of essay writing pedagogy in primary schools.